OPTIMALISASI ENERGI LISTRIK RUMAH HUNIAN SEDERHANA MBR SAMARINDA MELALUI STANDAR TEKNIS NASIONAL - Dimas Bintang Mudrajad; Prasetyo , Prasetyo (Journal of Innovation Research and Knowledge, 2025)
The growing demand for housing among low-income communities (MBR) in Samarinda requires the design of simple dwellings that are not only affordable but also energy-efficient, particularly in terms of electricity consumption. Excessive electricity use in poorly designed MBR houses contributes to the increasing urban energy load. This study aims to optimize electricity consumption in the design of simple MBR housing through the application of National Technical Standards. A quantitative descriptive method was employed, using comparative energy consumption simulations based on existing designs and proposed models that adhere to technical standards. Data were collected through field observations, literature review, and energy modeling using building simulation software. The results show that applying technical standards related to building orientation, natural ventilation, and the appropriate use of roofing and wall materials can reduce electricity consumption by 25–35% compared to the original designs. These findings indicate that integrating technical standards into the design of simple housing has a significant impact on energy efficiency and reducing household electricity costs. Therefore, this approach is crucial to be adopted in housing policy for low-income communities in tropical regions such as Samarinda.